Vitaceae endémicas del Perú - León, Blanca (2006)
The Vitaceae are represented in Peru by three genera and 31 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all vines and lianas. Here we recognize one endemic species in the genus Cissus. This species is found in Humis Lowland Amazonian Forests region, to 200 m elevation. It has not been recorded within Peru’s protected areas system.